2014
DOI: 10.1097/01.aog.0000447417.71070.10
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Human Papillomavirus 16/18 Genotype Risk Stratification in Atypical Squamous Cells of Undetermined Significance in an Inner-City Urban Hospital

Abstract: analyses were used to identify risk factors for the development of varicella zoster virus-related morbidity and mortality. RESULTS:We identified 935 patients admitted for varicella zoster virus infection among 7.7 million pregnancy admissions, representing an incidence of 1.21 cases per 10,000 pregnancies (95% confidence interval [CI] 1.13-1.29). The incidence of varicella zoster virus pneumonia was 2.5% (95% CI 1.6-3.7). There were no maternal deaths recorded during the 8-year study period. There were no sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The pathogenesis of HPV is dependent on a number of factors, but it is now understood that certain genotypes of the virus are more closely associated with the development of severe disease, including cancer. HPV genotypes are commonly separated into two broad categories, (i) "low risk" (types 6,11,40,42,43,44,53,54,61,72,73, and 81) and (ii) "high risk" (types 16,18,31,33,35,39,45, 51, 52, 56, 58, 59, 66, and 68), based on the degree of correlation between infection and the development of cervical cancer. Among the 14 high-risk (HR) genotypes, HPV-16 and HPV-18 have been estimated to account for approximately 70% of cervical cancers (2).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The pathogenesis of HPV is dependent on a number of factors, but it is now understood that certain genotypes of the virus are more closely associated with the development of severe disease, including cancer. HPV genotypes are commonly separated into two broad categories, (i) "low risk" (types 6,11,40,42,43,44,53,54,61,72,73, and 81) and (ii) "high risk" (types 16,18,31,33,35,39,45, 51, 52, 56, 58, 59, 66, and 68), based on the degree of correlation between infection and the development of cervical cancer. Among the 14 high-risk (HR) genotypes, HPV-16 and HPV-18 have been estimated to account for approximately 70% of cervical cancers (2).…”
mentioning
confidence: 99%
“…According to the American Society for Colposcopy and Cervical Pathology (ASCCP) and the American Society for Clinical Pathology, women 30 to 65 years of age may be screened by routine cytology (Pap smear) every 3 years or by both cytology and an approved HPV test every 5 years. Importantly, specific genotyping for HPV-16 and -18 is now recommended for patients Ն30 years of age who test positive for HR HPV but negative by cytology because of the increased probability that HPV-16-and/or HPV-18-positive patients will develop cervical dysplasia (6). Recent data have shown that the absolute risk that HPV-16-and/or HPV-18-positive women will develop high-grade (CIN2) or worse (CIN2ϩ) cervical intraepithelial neoplasias is nearly 2-fold greater (11.4% versus 6.1%) than that for women positive for "other" HR HPVs and Ͼ10-fold higher (11.4% versus 0.8%) than that for women who are negative for HR HPV (7).…”
mentioning
confidence: 99%